Enhancing Resource Efficiency in BRICS through Fintech: A Multi-Dimensional Analysis of Green Growth and Socio-Economic Impacts - Salim, Ansa Savad; Keong, Ooi Chee; Bindabel, Wardah Abdulrahman; Mirzaliev, Sanjar (International Journal of Energy Economics and Policy, 2025)
Resource efficiency entails eliminating waste and managing natural resources wisely in order to minimise environmental harm and sustain it over time. It postulates as the intersection of modern technology and financial services has emerged as a catalyst for revolutionary change across a variety of industries. It can optimise financial transactions, simplify supply chains, and promote sustainable investing practices, which have the ability to transform economic paradigms and make resource efficiency simpler. The study aims to investigate the impact of FinTech Innovation, green growth, and economic and social development on resource efficiency in BRICS countries covering the period 1998 to 2022. To analyse the relationship between the variables, the Cross sectional Autoregressive Distributed Lag Model (CS-ARDL) and recently introduced Method of Moments Quantile regression (MMQR) approaches are used. The findings of the study reveal the positive association of green growth and social development with natural resource efficiency, however, results suggest the negative association between economic growth and resource efficiency. In contrast, fintech is not found to have any significant impact on resource efficiency. As a robustness check, the findings of MMQR estimation approach validate the estimation findings of the CS-ARDL analysis with significance of the variables varying at different quantiles. The findings suggest a need for strategic interventions and policy measures that prioritize investment toward the upswing thrust in FinTech innovation, green growth initiative, social development activities and environmentally sustainable practices. Policymakers in BRICS countries need to bolster their financial technology infrastructure, educate the public about its advantages and foster the collaborations between government and financial sector entities to leverage the positive impacts of FinTech on sustainable development. Similarly, ensuring economic policies are motivated by green growth practices that are aligned with resource efficiency goals should be at the center of their purview.